Median Arcuate Ligament Syndrome: From Diagnosis to Multidisciplinary Management—A Narrative Review - Patryk Skórka; Jacek Szulc; Konrad Szewczyk; Adam Szafirowski; Piotr Gutowski; Maciej Wojtuń; Paweł Rynio (Journal of Vascular Diseases)
Median Arcuate Ligament Syndrome, also known as Dunbar’s syndrome, is a rare condition caused by stenosis of the celiac artery (CAS) through the fibrous arch connecting the diaphragmatic branches. It manifests as postprandial abdominal pain, nausea, vomiting, weight loss and increased epigastric tenderness. The condition most commonly affects young females without coexisting vascular comorbidities. Diagnosis is difficult due to the non-specific symptoms, often overlapping with other gastrointestinal diseases. Standard investigations include duplex ultrasound, computed tomography angiography (CTA) and contrast-enhanced magnetic resonance imaging (CE-MRA). Treatment mainly consists of surgical release of the arch ligament, which can be performed by open, laparoscopic or robotic methods. Surgery is often supported by celiac truncal stenting for residual stenosis, which significantly improves vascular flow. Alternative approaches include visceral plexus blocks and novel hybrid techniques, such as a combination of ligament release and endovascular treatment of the celiac trunk. In severe cases, vascular by-passes are recommended. The aim of this paper is to discuss the clinical manifestations, diagnostic possibilities, therapeutic options and directions for further research on MALS from the perspective of a vascular surgeon. It emphasizes the need for a multidisciplinary approach, including collaboration between the surgeon, radiologist, gastroenterologist and psychologist, which enables comprehensive disease management and improved quality of life for patients. In addition, the need for further development of diagnostic and therapeutic methods for early diagnosis and effective treatment was pointed out.